A theoretical investigation of solvent effect on the conformational equilibria of 2-substituted cyclohexanone ketal derivatives - Sağ-Erdem, Safiye. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1995., 1995)
The conformational equilibria of 6-substituted-1,4-dioxospiro-[4.5]decanes and 7substituted-1,5-dioxospiro [5.5]undecanes, relatively complex polar systems, with substituents X=-CH3, -F, -CI, -CN, -OH, -OCH3, -N02 have been studied. The complete geometry optimizations have been carried out sequentially in the gas phase and in solution to represent the effect of the solvent. The methodology consists of the semiempirical PM3 hamiltonian and the self consistent reaction field computations. The effect of the solvent is implemented by the "cavity model". Ab initio calculations have also been performed on 1 ,1 , 2-trihydroxy ethane as a model for the hydroxy derivatives of the ketals studied.The discussion of the results is focused on the solvent effects arising from structural aspects, steric and electrostatic interactions on the axial/equatorial relative stability. The role played by multipole moments is considered. Good agreement with available experimental data and with previous theoretical studies has been obtained in general. The semiempirical methods and the simple solvent models are useful to predict the main role of solute-solvent interactions in conformational equilibria of complex systems for which ab initio calculations cannot be performed.
Keywords: Conformational analysis.